The decline of the globally threatened Rudd's Lark in one of its last remaining core sites, the Wakkerstroom grasslands - Gush, Wesley Gurney (Percy FitzPatrick Institute of African Ornithology, 2017)
Abstract The Rudd's Lark Heteromirafra ruddi is a globally threatened species with a fragmented population occurring in one of the world's most poorly-protected biomes, the grasslands. This, together with its endemism to the Highveld of South Africa and climate envelope modelling which predicts a dramatic reduction in its available habitat, places the species firmly in the cross-hairs of extinction risk. This thesis aims to gain a better understanding of Rudd's Lark population trends, habitat preference and threats in one of its most important remaining core sites in the grasslands around Wakkerstroom, Mpumalanga Province, which are under private ownership and used predominantly for grazing. My objectives were, first, to determine whether the species has declined in the Wakkerstroom area since a survey conducted in 2002 by David Maphisa. Second, to determine what habitat variables predict Rudd's Lark incidence, whether there has been a change in its available habitat and in farm management practices, and whether the species has changed in its habitat selection since the previous survey. Finally, I aimed to investigate whether other grassland birds (particularly other threatened grassland endemics) also respond to fine-scale habitat variation and share habitat preference with the Rudd's Lark. I found both absolute lower numbers of Rudd's Larks (5 transects with Rudd's Lark present down from 9 in 2002; 9 individuals down from 32), and a lower probability of encounter (significantly lower in the case of individuals). Seven transects had been lost to crop production, two of which formerly contained Rudd's Larks. Forb and dead vegetation cover had significantly increased at a coarse scale, but vegetation variables did not explain any significant variation in Rudd's Lark incidence at either a fine or a coarse scale within 2016. However, Rudd's Larks appear to be occupying subtly different habitat now compared to 12 years ago: lark territories surveyed in 2016 had less bare ground and more but shorter grass cover than in 2002. Most farmers reported warmer conditions in recent years and that burning generally took place between August and October, matching the analysis of remotely-sensed fire data from the past ten years and implying that destructive late-season fires are not common. Correspondingly, I found that burning regimes did not predict Rudd's Lark incidence. Among other threatened grassland species, Yellow-breasted Pipits showed a clear preference for taller grass and higher altitudes, unlike Rudd's Larks which showed no detectable preferences. In summary, direct loss of grassland habitat through conversion to crops appears to be a pressing threat to Rudd's Larks, although the species has also declined within the remaining area of grassland habitat. The specific drivers of this decline remain unclear given that the observed changes in grassland structure since 2002 do not correspond with Rudd's Lark habitat selection. Taken together, these findings are very concerning given that the Wakkerstroom area is considered to be one of the last remaining core sites for the species, and call its IUCN threat status of globally Vulnerable into question. A priority for future research will be to understand what limits Rudd's Larks to its current pockets of occupancy within its remaining apparently suitable grassland habitat, and whether increasing grassland fragmentation will accelerate its decline. Key words: fire, grassland, habitat selection, Heteromirafra ruddi, IUCN status, rangelands, Rudd's Lark, threatened species, transects